MAHASISWA DAN MASYARAKAT BERSINERGI BERSATU DAN BANGKIT BERSAMA DI MASA PANDEMI COVID-19 - Aji Permana Putra; Paiman Paiman; Nur Halimah (Gemi: Jurnal Penelitian dan Pengabdian, 2022)
Thematic KKN with the theme "United and Rising Together with the Community in the Covid-19 Pandemic Period" is a form of education by providing learning experiences for students to train students to increase their capacity by being directly involved and participating in efforts to help the community to prevent, break the chain of the spread of COVID -19, educating people in their own villages/villages/regions to stay alert, keep active by not forgetting the health protocols during the Covid-19 Pandemic, as well as creating a green environment to reduce and prevent global warming and flood disasters due to reduced green land in the community. . The purpose of this activity program is education about preventing COVID-19 with social assistance in the form of distributing basic necessities to the affected poor, as well as making hand soap, planting trees, distributing masks and hand sanitizers, providing vitamins and isoman needs, and planting tree seeds for preparation of group III reforestation program.